Avaliação por meio de tomografia computadorizada de feixe cônico dos resultados pós-cirúrgicos de dentes autotransplantados - Intra, Tereza Jacy da Silva Almeida (2023)
Autotransplantation may favor the treatment of children who have experienced trauma. Most of the success of self-transplanted teeth happens in the age group between 7 and 13 years old. Considering that at this age, the rehabilitation of these children is difficult, since most treatments would interfere with craniofacial growth and development, autotransplantation is highlighted and the scientific literature already proves this. In this study, after approval by the ethics and research committee, 23 patients who had already undergone autotransplantation treatment performed at the Dental Trauma Project of the Brazilian Association of Dentistry of Espírito Santo (ABO-ES) participated. All guardians signed the Free and Informed Consent Term (TCLE) to enable the evaluation through tomographic analysis. In all, 30 teeth were analyzed using Cone Beam Computed Tomography. All images, in DICOM format, were properly analyzed by three previously calibrated evaluators (one radiologist and two endodontists) using the Prexion Viewer program (Terarecon, San Mateo, CA, USA). The main post-surgical results considered were pulpal and periodontal repair. All teeth were premolars and 04 teeth were submitted to endodontic treatment. In 16 teeth the pulp chamber was completely obliterated, 06 teeth partially obliterated and 04 teeth with normal pulp chamber. 21 teeth with partially calcified canal and 02 with completely obliterated canal. 03 teeth with normal aspect and 01 tooth presented internal resorption. The periodontal space and lamina dura were preserved in 29 teeth and absent in only 01 tooth. Images of inflammatory resorption were observed in 09 teeth and 01 specimen showed substitutive resorption. 10 teeth had unchanged apical periodontium, 10 teeth had periapical lesions, 08 teeth had increased periodontal space and 15 teeth had apical resorption. Root development was complete in 24 teeth and incomplete in 06 teeth. When considering the follow-up of these individuals, these were divided into: 3-5 years, 5-10 years and for more than 10 years. However, when the data of the variables contained in the study and the follow-up time were crossed, no statistical significance was observed. Considering the results and analyses, it can be concluded that the self-transplanted teeth present favorable results regarding pulpal and periodontal repair, remaining viable and integrated to the new site, in all specimens.